2016
DOI: 10.1080/10409238.2016.1237934
|View full text |Cite
|
Sign up to set email alerts
|

Decoding P4-ATPase substrate interactions

Abstract: Cellular membranes display a diversity of functions that are conferred by the unique composition and organization of their proteins and lipids. One important aspect of lipid organization is the asymmetric distribution of phospholipids across the plasma membrane. The unequal distribution of key phospholipids between the cytofacial and exofacial leaflets of the bilayer creates physical surface tension that can be used to bend the membrane; and like Ca2+, a chemical gradient that can be used to transduce biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 103 publications
0
31
0
Order By: Relevance
“…On the other hand, the P335L mutation alters the first residue of a highly conserved PISL motif in the fourth transmembrane domain (M4). The M4 transmembrane domain, based on a modelled structure of the human P4 ATPase ATP8A2 and related mutational studies, is proposed to play a critical role in determining the specificity of the lipid substrate, with the isoleucine residue in the PISL motif contacting the head group of the phospholipid substrate and mediating its release to the cytoplasmic side and the M4 domain serving as a pump rod to move the phospholipid substrate (Andersen et al, 2016;Vestergaard et al, 2014;Roland and Graham, 2016). Interestingly, a missense mutation (I376M) in the PISL motif in ATP8A2 was found to cause a neurodegenerative disorder in humans (Onat et al, 2013) and found to impair the ATPase and the PS flipping activity of ATP8A2 without affecting its expression or stability in cultured cells (Vestergaard et al, 2014), further highlighting the importance of this motif in P4 ATPases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the P335L mutation alters the first residue of a highly conserved PISL motif in the fourth transmembrane domain (M4). The M4 transmembrane domain, based on a modelled structure of the human P4 ATPase ATP8A2 and related mutational studies, is proposed to play a critical role in determining the specificity of the lipid substrate, with the isoleucine residue in the PISL motif contacting the head group of the phospholipid substrate and mediating its release to the cytoplasmic side and the M4 domain serving as a pump rod to move the phospholipid substrate (Andersen et al, 2016;Vestergaard et al, 2014;Roland and Graham, 2016). Interestingly, a missense mutation (I376M) in the PISL motif in ATP8A2 was found to cause a neurodegenerative disorder in humans (Onat et al, 2013) and found to impair the ATPase and the PS flipping activity of ATP8A2 without affecting its expression or stability in cultured cells (Vestergaard et al, 2014), further highlighting the importance of this motif in P4 ATPases.…”
Section: Resultsmentioning
confidence: 99%
“…P4-type ATPases are highly conserved transmembrane proteins that are suggested to promote ATP-dependent inward movement of aminophospholipids such as PS (Auland et al, 1994;Tang et al, 1996;Paulusma and Oude Elferink, 2005;Andersen et al, 2016;Roland and Graham, 2016), resulting in the restriction of PS in the cytosolic leaflet and PS asymmetry in the plasma membrane. The mechanisms by which these large lipid substrates are transported specifically across the membrane have remained an enigma (Vestergaard et al, 2014;Andersen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Combining the finding of two substrate binding sites and the transport cycle, we propose that the lipid head group transports through the groove between TMH2 and TMH4, while lipid tails move accordingly on the hydrophobic surface of the TM2 and TM4. This is essentially the same as the previously described "credit card model" (Andersen et al, 2016;Roland and Graham, 2016).…”
Section: Transport Mechanisms Of the Class-3 And Class-1 P4 Atpases Amentioning
confidence: 85%
“…TM1-6 have been suggested to form the principal unit responsible for transport of phospholipids across bilayers, whereas TM7-10 seem to play an ancillary role (30-32, 59-61). Three hypotheses have been proposed to describe the mechanism underlying substrate transport by P4-ATPases: 1) a 2-gate model, 2) a hydrophobic gate model, and 3) a central cavity model (32,(59)(60)(61)(62). The 2-gate model suggests that entry and exit gates at the interface of the exoplasmic and cytoplasmic membranes, respectively, sequentially bind to and transfer specific substrates by using TM1-4 (60).…”
Section: Lipid Transport By P4-atpasesmentioning
confidence: 99%
“…Three hypotheses have been proposed to describe the mechanism underlying substrate transport by P4-ATPases: 1) a 2-gate model, 2) a hydrophobic gate model, and 3) a central cavity model (32,(59)(60)(61)(62). The 2-gate model suggests that entry and exit gates at the interface of the exoplasmic and cytoplasmic membranes, respectively, sequentially bind to and transfer specific substrates by using TM1-4 (60). The hydrophobic gate model proposes that a cluster of hydrophobic residues centered around the middle of TM4 propels water in a groove between TM1, TM2, TM4, and TM6 together with the phospholipid headgroup to the cytoplasmic side (59).…”
Section: Lipid Transport By P4-atpasesmentioning
confidence: 99%